Ethanolic extract cream of red cabbage (Brassica oleracea L. var. capitata f.rubra) on the epidermal thickness in Wistar rats (Rattus norvegicus) after ultraviolet-B exposure - Yogarani V.C Rajappan; I Gusti Kamasan Arijana; I Wayan Sugiritama; IGA Dewi Ratnayanti (Intisari Sains Medis, 2018)
Background: UV exposure is related to oxidative stress and also as an essential factor in skin photoaging. Several antioxidants are widely used in preventing skin photoaging by influencing epidermal skin layer. High concentrations of antioxidant properties in red cabbage are known to have these effects. This study aims to determine the role of ethanolic extract cream of red cabbage on the epidermal thickness in Wistar rats after UV-B exposure.Methods: An experimental study was carried out among 25 Wistar rats which divided into 5 groups as follows: P1 as control (only exposed to UB-B), P2 (placebo and UV-B), P3 (5% ethanolic extract cream and UV-B), P4 (10% ethanolic extract cream and UV-B), and P5 (20% ethanolic extract cream and UVB). The UV-B dosage applied for each group was 65 mJ/cm2. The thickness of epidermis is calculated by direct measurement using Image Raster software from basal membrane to stratum corneum. The statistical analyses were performed using SPSS ver. 20.0.Results: There was a significantly different in the epidermal thickness among groups (P < 0.05). The mean of epidermal thickness in the control group (P1) was 36.00±1.08 µm, followed by 27.66±0.87 µm in the treatment group I (P2), 26.76±1.02 µm in the treatment group II (P3), 24.94±1.25 µm in the treatment group III (P4), and 20.24±1.47 µm in the treatment group IV (P5).Conclusion: The ethanolic extract cream of red cabbage (Brassica oleracea L.Var. capitata f. rubra) in different doses have a statistically significant impact on the epidermal thickness in Wistar rats after UV-B exposure.